Graphical models for security : third International Workshop, GraMSec 2016, Lisbon, Portugal, June 27, 2016, Revised selected papers /: third International Workshop, GraMSec 2016, Lisbon, Portugal, June 27, 2016, Revised selected papers. (2016) - Unknown
No abstract available